Day's goby, Acentrogobius dayi Koumans, 1941 (Pisces: Gobiidae) in the desert Sawa Lake, south-west Baghdad, Iraq. (6th October 2015) - Ziyadi, Mustafa S.F.; Jawad, Laith A.; Almukhtar, Mustafa A.; Pohl, Thomas
Abstract : Three adult specimens of the fish species Acentrogobius dayi were collected from Sawa Lake, south-west of Baghdad, Iraq. The current report represents the first record of A. dayi from Sawa Lake and from other inland water bodies of Iraq.